AngioJetTM rheolytic thrombectomy induced intravascular haemolysis leading to Acute Kidney Injury requiring Dialysis - Sebastian, Hultin; Tam, Nguyen; Karumathil, Murali (Journal of Clinical Nephrology, 2018)
Background: AngioJetTM rheolytic thrombectomy has been used in the treatment of deep vein thrombosis (DVT) to prevent post-thrombotic syndrome. Though not widely appreciated, it has the potential to cause intravascular haemolysis. Report: A 37 year old man with no previous medical history presented to his GP with a three week history of progressive right upper limb swelling. Doppler imaging confirmed right upper limb DVT and CT scan demonstrated thoracic outlet syndrome. The patient underwent AngioJetTM thrombectomy followed by IV heparin infusion. Successful revascularisation of the occluded vein was achieved. Overnight he developed haematuria, which was initially attributed to IV heparin. Urinalysis however revealed no red cells or casts. Apart from an Hb drop from 134 to 117 his blood profile and blood film showed no abnormality. He subsequently developed progressive oliguria with marked oedema and acute kidney injury (AKI). His creatinine peaked at 1070umol/l at 96 hours post procedure and he was started on intermittent dialysis. He remained dialysis dependent for 6 days. Ultrasound imaging excluded urinary obstruction. Autoimmune and vasculitic serology were negative. Intravascular haemolysis and haemoglobinuria was confirmed by raised LDH (1714u/L) and low haptoglobin (<0.1units). Direct Coomb’s test, Cold agglutinin test and paroxysmal nocturnal haemoglobinuria screen were negative. The patient’s renal function normalised over 3 months. Conclusions: The likely cause of this man’s AKI is heme pigment nephropathy from intra-vascular haemolysis. Increased awareness of this condition may allow early identification and intervention to reduce the risk of renal injury from AngioJetTM associated haemolysis.